Trophic Guild Structure of a Canopy Ants Community in a Mexican Tropical Deciduous Forest - Gabriela Castaño-Meneses (Sociobiology)
Ants constitute a very important element in the canopies of tropical forest. The species richness, composition and diversity of ant canopy community in a tropical deciduous forest in the Pacific Cost of Mexico was studied. The sampling was performed by fogging method in a watershed of the Chamela Biological Station, Jalisco State, Mexico. Ants represented 0.5% of all invertebrates in the tree canopy of Chamela, and a total of 46 ant morphospecies from 17 genera were collected. Camponotus and Cephalotes contributed with 13 and 6 species respectively, and the most abundant ants were species of Crematogaster, Tapinoma, Cephalotes and Camponotus. Ant composition was broadly similar at the two sites, and on different canopy species, although significant differences in abundance were apparent for some individual ant species. The dominant guild in the canopy was the omnivourous in all study, but differences in guild trophic composition were recorded in each fogging. The ant community in the canopy of Chamela has shown low spatial variation, but the composition of ant species and trophic guilds have important seasonal variations, demonstrated variations in the exploitation of resources along the year, and vertical migrations of ant species from soil and shrub layer to canopy in the tropical deciduous forest.